EFEKTIVITAS PENAMBAHAN NUTRIEN DAN MANIPULASI CAHAYA UNTUK MENINGKATKAN PRODUKSI DAN KUALITAS AGAR Gracilaria sp. - Eka Rosyida; Nasmia Nasmia (Universitas Tadulako, 2015)
Nutrient enrichment and environmental manipulation in this study were aimed to enhance the growth and quality of Gracilaria sp. Enrichment treatments were N: P ratio of 10:0 (A), N: P ratio of 10:1 (B), N: P ratio of 5:1 (C) and no nutrient added (D) with stocking density of 800 g per culture media and water depth of 50 cm in week I-IV. Light manipulation as water depth variation was conducted in week V-VI. Completely randomize design was employed with 6 and 2 replication in week I-IV and week V-VI, respectively. The results showed no significant effect of treatments on the growth of seaweed (ANOVA, P> 0.05), however DGR maximum indicated by treatment B. The highest water content of the dried Gracilaria <24%, while the average ash content for all treatments <33%. In general, higher agar yields were obtained from non-enriched treatment (D) and treatment with a depth of 80 cm. Key words : Disease, enrichment, Gracilaria sp. manipulation, seaweed active extract.